PPO.60 Risk of preterm delivery with increasing depth of excision for cervical intraepithelial neoplasia in England: nested case-control study. (9th June 2014) - Castanon, A; Landy, R; Brocklehurst, P; Evans, H; Peebles, D; Singh, N; Walker, P; Patnick, J; Sasieni, P
Abstract : Background: Meta-analyses show an association between excision of cervical intraepithelial neoplasia and preterm delivery. However, the precise role of depth of excision is unclear. Methods: We carried out a cohort study (phase 1) with a nested case-control study (phase 2) using record linkage. We identified women with a histological sample taken at colposcopy between 1989 and 2011 who were then linked by HES (Hospital Episode Statistics) to hospital obstetric records to identify live births. Full colposcopy details and pathology reports were obtained. Women with preterm deliveries (20–36 weeks) were frequency matched to women with term births (38–42 weeks). The association between depth of excision and risk of preterm birth was analysed using inverse probability weighted relative risk regression. Analyses were appropriately adjusted for known confounders. Findings: Of 956 preterm births (cases), 198 (21%) were very/extremely preterm (20–31 weeks). 558 cases (58%) gave birth after excision compared to 556 of 1039 controls (54%). We will present relative and absolute risks of preterm birth among women with small (<10 mm), medium and large excisions (15+mm). We will report on whether multiple excisional treatments carry an additional risk beyond the summed depths of individual treatments. These results will also be shown for very/extremely preterm births. Interpretation: To assess whether there is a depth of excisions bellow which there is no increased risk of preterm birth compared to those who receive a diagnostic biopsy only.